A Model-Based Simulator for Content Delivery Network using SimEvents MATLAB-Simulink - Erwin Harahap; Icih Sukarsih; Gani Gunawan; M Yusuf Fajar; Deni Darmawan; Hiroaki Nishi (Universitas Lampung, 2016)
Abstract—Simulation methodology has become popular among network researchers due to the availability of various sophisticated and the flexibility of simulation packages in model construction and the result’s validation. The objective of our research is to introduce a discrete simulator tools known as SimEvents toolbox that runs on MATLAB-Simulink with the advantages of graphical user interface (GUI) system and a total customized simulator design. In this paper, we design a model-based network simulator named as “CDNlink”. CDNlink is designed based on a queuing model and functioned to study the content delivery networks (CDN). As a result, we have designed the simulator for Client, Router, DNS, and Server. Moreover, we simulate the CDN system for packet round trip time (RTT) and server’s queue length.Keywords—simulink, content delivery network, model-based simulation, simevents, cdnlink.